HUBUNGAN PROFESIONALISME GURU DENGAN PRESTASI BELAJAR AL-QUR’AN HADITS SISWA DI MADRASAH TSANAWIYAH GUPPI SUMBEREJO TANGGAMUS : INDONESIA - Muhtarom, Muhtarom; Mahmudah, Mahmudah; Evi Gusliana (JOURNAL MANAJEMEN PENDIDIKAN ISLAM AL IDARAH, 2016)
Abstrac The development of education is increasingly in need of management system that good.For the development of education in need of people who was really experts in their fields. Profession is essentially a job that requires knowledge and skills that are highly qualified to serve or serves the public interest to achieve human well-being, especially in the field of education. This research generally aims to collect information on efforts to improve teacher profesionalisme of Qur'an hadith lesson in MTs GUPPI district Sumberejo Kab.Tanggamus. This study was conducted on 38 students MTs GUPPI Sumberejo (34%) as a sample of the student population as much as 117 which consists of class VII, VIII, and IX class and subject teachers of the Qur'an and hadith. Data were collected by observation, interview, documentation, and questionnaires, while data analysis using chi square statistic. Based on the analysis of data obtained count value X is greater than X tables, both at 1% significance level or at the level of significance of 5%. Thus Ho is rejected, which means there is the influence of professionalism of teachers on learning achievement quran hadith students. To determine the independent variables (Professional Teacher) and dependent variable (Achievement Qur'an Hadith Students) koefisienkontingensi then calculated using the formula (KK) or C, from the calculations, the price of C = 0.514 and compared Cmax = 0,816. When seen in the table there is a contingency coefficient values between 0.290 to 0.578, it can be concluded that there is a fairly close relationship between the two variables. Keywords: Professionalism, Teacher, Achievement, Learning